Study on Early Childhood Adversities of Orphans Rearing in Orphanages (Bangladesh Medical Journal, 2021)
Orphans spread a significant mass of our absolute child folks and this study was planned to determine the early childhood adversities of orphans that may attract them in various violence and perilous fortune lead further that in the end have a long-standing psycho-social impact on their adulthood. This was a cross-sectional study that was completed among 301orphans of both genders. The subjects were chosen by convenient sampling technique based on specific inclusion criteria and maintaining ethical issues. The study was directed from January to December 2017 in different orphanages of Chittagong and Dhaka city. The examination uncovered, maximum (84%) of participants were male and the rest (16%) were female. Among them, around 44.9% of them were matured from 10-12 years followed by 37.9% matured between 13-15 years. The majority (62%) of the participants had education up to primary/equivalent level. A maximum (69.77%) of them lost their father and 17.94% of them lost both of their parentages. The study revealed, physical assault (30.2%), serious domestic accident (27%), and life-threatening illness/injury (33.6%) had higher frequencies than other events that happened with the participants personally. Additionally, events like traffic transportation accidents (47.3%), serious domestic accidents (36.8%), and physical assault (28.3%) had higher frequencies than other events experienced through observing to transpiring. Then again, transportation accidents, domestic accidents (ꭓ2 =32.673, p